PENGARUH LAMA PAPARAN PESTISIDA TERHADAP GANGGUAN HATI PADA PETANI DI SUSUN PARITAN DESA SUDIMORO KECAMATAN MENGALUH KABUPATEN JOMBANG - Nesa Emilia Maretha; Andreas Putro Ragil Santoso, S.Si., M.Si; Nur Izzatul Awaliyah; Dra. Wieke Sri Wulan, S.T., MARS., M. Kes (Universitas Nahdlatul Ulama Surabaya, 2020)
The World Health Organization (WHO) states that every year 1–5 million cases of pesticide poisoning occur in agricultural workers with a death rate of up to 220,000. The accumulated pesticides that enter the liver cannot be broken down and excreted, so they will be stored in the liver and cause organelle or cell disorders in the liver. This results in damage to the liver parenchyma or impaired liver cell membrane permeability so that free enzymes leave the cell. This study aims to determine the effect of the duration of exposure to pesticides on SGOT and SGPT levels in petroleum. The results obtained from 12 samples of pesticide spraying farmers who have been tested for SGOT and SGPT levels are still within normal limits. The results statistically using the Two Way Anova test obtained a significant value of p (0.656)> α (0.05) in the length of exposure, so there was no difference in the levels of SGOT based on the length of exposure. Obtained a significant value p (0.068)> α (0.05) in the length of exposure, so there is no difference in the levels of SGPT. It can be concluded that the duration of exposure to pesticides on liver function disorders in farmers does not have a significant effect between the length of exposure and liver function disorders.